2015
DOI: 10.24059/olj.v19i4.549
|View full text |Cite
|
Sign up to set email alerts
|

Online Master's Students Perceptions of Institutional Supports and Resources: Initial Survey Results

Abstract: This article presents the quantitative findings of an exploratory mixed methods study that investigated first-and second-year online graduate master's students': 1) perceptions of the importance of, and satisfaction with, administrative, academic, technical, and online community supports; 2) personal factors and grit level; and 3) differences, if any, that existed among students, in these areas. Findings showed that a large majority of students rated course-level supports (e.g., instructor support, embedded he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 33 publications
4
18
0
Order By: Relevance
“…Many institutions utilize student satisfaction surveys to assess responsiveness. Milman, Posey, Pintz, Wright, and Zhou () conducted a needs assessment in an online master's program to discover how students used existing support services and if there were differences in use between groups of students. A team at another institution interviewed 19 online students and five student affairs staff members to explore online undergraduate students’ perceptions of staff support (Taylor & Holley, ).…”
Section: Specific Student Experiences To Monitormentioning
confidence: 99%
“…Many institutions utilize student satisfaction surveys to assess responsiveness. Milman, Posey, Pintz, Wright, and Zhou () conducted a needs assessment in an online master's program to discover how students used existing support services and if there were differences in use between groups of students. A team at another institution interviewed 19 online students and five student affairs staff members to explore online undergraduate students’ perceptions of staff support (Taylor & Holley, ).…”
Section: Specific Student Experiences To Monitormentioning
confidence: 99%
“…Previous literature on the use of course-based learning support and unique services, such as the writing center, career services, and the bookstore, found that many students perceived course-level support (faculty members, tutoring, and library services) as important, while fewer students indicated that resources needed for the unique services were important (Milman, Posey, Pintz, Wright, & Zhou, 2015). Many of the participants in this current study explained the necessity of the writing center for their success, persistence and program completion.…”
Section: International Student Perceptions Of the Writing Centermentioning
confidence: 83%
“…writing center, career services, bookstore) were important (Milman, Posey, Pintz, Wright, & Zhou, 2015). The researchers recommended that their institution consider writing coaches be assigned to students for specific courses, rather than having a centralized writing center (Milman, et.…”
Section: International Student Support Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…How do eSupervisors contribute to the learning growth of eInterns? Research on online graduate students' levels of importance and satisfaction has highlighted career services as an area of focus for potential improvements (Milman, Posey, Pintz, Wright, & Zhou, 2015).…”
Section: Statement Of the Problemmentioning
confidence: 99%